How equitable is access to opportunities and basic services considering the impact of the level of service? The case of Santiago, Chile - Ignacio Tiznado-Aitken; Juan Carlos Mu\~noz; Ricardo Hurtubia (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2016)
Cities face the daily challenge of providing people with access to different activities through their public transport systems. Despite its importance, there is little research on accessibility that focuses on the use of this mode and even less accounting for the impact of level of service (i.e. travel time, waiting time, reliability, comfort and transfers). Thus, the aim of this paper is to propose a methodology to determine how access to opportunities and basic services through public transport systems is distributed in cities, and how the perceived level of service decreases or accentuates the existing gaps. Three indicators are calculated for Santiago based on data from public transport operations, smart card validations and georeferenced information: walking accessibility to public transport stops considering the quality of urban furniture, safety and environment; connectivity provided by the system in each area to the rest of the city considering the level of service through a measure of generalised time (in-vehicle time); and a measure of attractiveness of the destinations, based on number of trips attracted by purpose. The methodology is applied to a case study in Santiago, a highly unequal and segregated city. The results show that the accessibility gap between disadvantaged areas and more wealthy neighborhoods of the city increases if the user's perception of level of service for public transport is considered. We show that the three proposed indicators provide different dimensions of accessibility suggesting how and where to intervene to effectively improve equity. Thus, the indicators could be used to assist the prioritisation and focus of investment plans, the design process of urban policies or transport infrastructure and become a key input for planners and decision-makers.
Keywords: 330; Stadtverkehr; Kommunale Verkehrspolitik; Dienstleistungsqualität; Santiago (Chile); Chile